Nutritive Value of Mixed Cattle Feces with Several Level Coconut Residues Fermente by M4 - Islamiyati, Rohmiyatul (Buletin Nutrisi dan Makanan Ternak, 2014)
Nutritive value of mixed cattle feces with several levels coconut residues fermented by EM4.  This experiment used a completely randomized design of 4 treatment levels coconut waste (0, 10%, 20% and 30%), with 4 replicates in each treatment. All of treatments added 0.3% EM4  was activated and fermented semiaerob during 4 days. Physically the fermentation process were indicating a good process.  As a whole it can be concluded that increasing  of coconut residues levels up to 30% resulted in increasing estrac eter, while the contents of  crude fiber and crude protein  reduced significanly.